Testing the influence of various conditions on the migration of epoxidised soybean oil from polyvinylchloride gaskets - Hanušová, Kristýna; Rajchl, Aleš; Votavová, Lenka; Dobiáš, Jaroslav; Steiner, Ingrid (Food additives & contaminants. Part A, Chemistry, analysis, control, exposure & risk assessment, 2013)
Epoxidised soybean oil (ESBO) is widely used as a plasticiser and stabiliser mainly in food contact materials on the base of polyvinylchloride (PVC), especially in the gaskets of jar lids. PVC gaskets containing 10-37% of ESBO were prepared by the baking of PVC plastisols at various process temperatures (180-240°C) in the laboratory. ESBO migration into olive oil and 3% acetic acid was studied at various temperatures (4°C, 25°C, 40°C and 60°C) during a storage time up to 12 months. ESBO released into food simulants was transmethylated, derivatised and analysed by gas chromatography-mass spectrometry (GC/MS). The effect of food processing, i.e. pasteurisation (80°C and 100°C) and sterilisation (125°C) on ESBO migration was also evaluated. The results were critically assessed with respect to the test conditions of specific migration in accordance with the current European Union legislation (Regulation (EU) No. 10/2011). The levels of ESBO migration found confirmed that the test conditions (i.e. 40°C or 60°C, 10 days) representing contact in the worst foreseeable use scenario seem to be insufficient for the simulation of ESBO migration during long-term storage and thus do not provide satisfactory objective results.
Keywords: Plasticizers; Temperature; Plant Oils; Soybean Oil; Epoxy Compounds; Acetic Acid; chemické jevy; Chemical Phenomena; Polyvinyl Chloride; sójový olej; Time Factors; změkčovadla; kyselina octová; epoxidové sloučeniny; vysoká teplota; časové faktory; Food Packaging; oleje rostlin; teplota; obaly potravin; Hot Temperature; polyvinylchlorid